An investigation into the public health roles of community learning disability nurses. (31st August 2013) - Mafuba, Kay; Gates, Bob
<x xml:space="preserve">Abstract</x> Accessible summary People with learning disabilities find it difficult to get their health checked and to get information about their health. Community learning disability nurses play an important role in supporting people with learning disabilities to stay healthy. Community learning disability nurses support people with learning disabilities to get their health checked and to get information about their health. Summary International studies have shown poor uptake of public health initiatives by people with learning disabilities. In addition, studies have shown that people with learning disabilities experience poor access to public health services. The contribution of community learning disability nurses in meeting the public health needs of people with learning disabilities has evolved differently across the UK resulting in conflicting understanding of this role. This paper reports on a study that explored and explained the contribution of community learning disability nurses in the implementation of public health policies for people with learning disabilities. The study demonstrates that community learning disability nurses are involved in health surveillance, health promotion, health facilitation, health prevention and protection, health education, and healthcare delivery.